2013
DOI: 10.1111/desc.12080
|View full text |Cite
|
Sign up to set email alerts
|

Linking childhood poverty and cognition: environmental mediators of non‐verbal executive control in an Argentine sample

Abstract: Tests of attentional control, working memory, and planning were administered to compare the non-verbal executive control performance of healthy children from different socioeconomic backgrounds. In addition, mediations of several sociodemographic variables, identified in the literature as part of the experience of child poverty, between socioeconomic status and cognitive performance were assessed. Results show: (1) significant differences in performance between groups in most dependent variables analyzed - how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 44 publications
3
77
1
10
Order By: Relevance
“…18,75,76 In addition, 75 Although still limited and confined to individuals exposed to abuse, some evidence is emerging to support a similar role of caregiving in regulating gene expression in the human brain. 59,77 …”
Section: Brain Development and Sensitive Periodsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,75,76 In addition, 75 Although still limited and confined to individuals exposed to abuse, some evidence is emerging to support a similar role of caregiving in regulating gene expression in the human brain. 59,77 …”
Section: Brain Development and Sensitive Periodsmentioning
confidence: 99%
“…Material deprivation and stress are factors related to SES that may function as environmental mediators 59 of the SES-brain development relationship. Figure 1 draws on a framework based on animal neuroscience research advanced by Sheridan and McLaughlin, which posits that the environments of poverty shape neurodevelopment by depriving the brain of key stimuli and increasing its exposure to negative input.…”
Section: Environmental Mediators: Materials Deprivation and Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In Latin-American samples (Mexico, Argentina, Brazil), authors have found associations between parental education and the performance of children and adolescents (aged 3-13 years) in tasks of attention and verbal and visual memory (Villaseñor et al 2009), executive functions (Ardila et al 2005;Arán-Filippetti 2011;Lipina et al 2013) and written language (Cuadro and Balbi 2012). Brazilian studies that not found effects of SES on cognition (Lúcio et al 2010;Miranda et al 2007) or show relations in the opposite directions (Lúcio et al 2010) attribute these results to the sample characteristics or good quality of the schools (Lúcio et al 2010) and recognize that no other studies resembled they results.…”
Section: Introductionmentioning
confidence: 99%
“…Las zonas más estudiadas al respecto han sido el sistema prefrontal ejecutivo (Lipina et al, 2013) y el temporal mnémico (Farah et al, 2006).…”
Section: Conill Y a Montoya (1985)unclassified